Pseudomonas Exotoxin Immunotoxins and Anti-Tumor Immunity: From Observations at the Patient’s Bedside to Evaluation in Preclinical Models - Yasmin Leshem; Ira Pastan (Toxins, 2019)
Immunotoxins are protein drugs composed of a targeting domain genetically fused to a protein toxin. One killing domain being explored is a truncated Pseudomonas exotoxin A (PE). PE based immunotoxins are designed to kill cells directly by inhibiting their ability to synthesize proteins. However, observations from clinical trials suggest that this alone cannot explain their anti-tumor activity. Here we discuss patterns of clinical responses suggesting that PE immunotoxins can provoke anti-tumor immunity, and review murine models that further support this ability. In addition, we describe our preclinical effort to develop a combination therapy of local PE immunotoxins with a systemic anti-CTLA-4 immune check point blocking antibody. The combination eradicated murine tumors and prolonged the survival of mice. Clinical trials that test the ability of immunotoxins to augment immunotherapy have been recently opened.